ROLE OF SOCIETY IN CONVERVATION OF NATURAL RESOURCES - Singh, Sandhya (International Journal of Research -GRANTHAALAYAH, 2015)
Everyone has the right to live in this world and also every individual has responsibility to use natural resources judiciously. This will give equal opportunity to all to use the resources for the benefit of whole mankind. All living creatures belong to mother earth and they all have their shine of resources available. All these resources like land, energy, mineral, food, water, forest etc. have to be distributed in an equitable way for sustainable lifestyles of all creatures. Conservation of natural resources is now usually embraced in the broader conception of conserving the earth itself by protecting its capacity for self-renewal. Finally, the aim of this paper is to highlight the importance of the role of society members in the conservation of our natural or environmental resources.